Validation of the Algorithm in the Detection of the Image of a Person Based on the Control of a Lighting Device - Garcia-Quilachamin, Washington; Sanchez Cano, Julieta Evangelina; Pro Concepción, Luzmila; Santana Mantuano, Evelyn (International Journal of Online and Biomedical Engineering (iJOE), 2020)
This research has the objective to validate the effectiveness in the execution of the algorithm based on the detection of the image of a person, applied as a control in a lighting device, for better surveillance and energy efficiency in domestic and business areas. For the methodology was used the analysis of the data obtained in various video surveillance cameras with the algorithm integration. We considered, that the parameters such as the distance concerning the capture speed and its effectiveness in turning on and off a lighting device when detecting the image of a person are positive, false-positive, false-negative and negative were considered. concerning the data obtained, the results determined 99.5% of the image detection is positive. This is validated using the SPSS through the descriptive analysis, the analysis of the coefficient v. of Cramer (1) and the contingency coefficient (0.707).